The Implementation of Receivables Write-Off of the State-Owned Banks in Indonesia - Henrikus Renjaan (Hasanuddin Law Review, 2018)
This research reviews two issues: Firstly, it describes the imple-mentation of the receivable write-off of State-Owned Bank (BUMN Banks) in Indonesia, and secondly, it describes the relevance of the independence principles of directors and Good Corporate Governance to the implementation of receivables write-off of state-owned banks in Indonesia. This research uses normative and empirical juridical approaches. The normative approach includes research on the independence principles of directors and Good Corporate Governance to the implementation of receivables write-off of the state-owned bank, while empirical research is conducted to determine the process of claim abolishment by state-owned banks in Indonesia. The outcomes of the research indicate that the unresolved legal problem related to the state financial position in the state-owned banks due to conflict of public and private law norms causes the directors of state-owned banks have not dared to do the process of claim abolishment. Therefore, consi-dering that the principle of autonomy of directors and good corporate governance is enforced properly, no one is concerned about the risk of corporate policies related to the process of claim abolishment from a state-owned bank because, in its very essence, it is a Business Judgment Rule in the banking business practice.